Road and Rail Transport Infrastructure in the Philippines: Current State, Issues, and Challenges - Adoracion M. Navarro; Jokkaz S. Latigar (Philippine Institute for Development Studies (PIDS), 2022)
This study assesses the state of the country's road and rail transport infrastructure, identifies issues and challenges in the implementation of the public road and rail transport infrastructure program, and generates policy insights based on the analysis. Quantity and quality indicators show that the Philippines continues to suffer from inadequate and poor-quality road and rail transport infrastructure. In most metrics of comparison with ASEAN neighbors, the Philippines is also behind in improving the quantity and quality of its road and rail transport infrastructure. The assessment of targets and achievements in the Philippine Development Plan, the Public Investment Program, and the expenditure program reveals that many of the targets were not met. The low absorptive capacity, as indicated in unmet expenditure targets, of the major agencies in charge of the road and rail transport sector suggests problems in implementation. Digging deeper into the implementation challenges, the study finds that the persistent problems are right-of-way acquisition, financing, political intervention, weak capacity at the local government level, natural calamities, and project management issues. There were also newly introduced problems, such as the adverse effects of the pandemic on the materials and manpower supply chain and the difficulty of implementing projects with delayed releases of funds. To help address these problems, the study offers policy insights. It would be ideal for Congress to enact a long-term national transport plan but in the meantime, strict adherence to the principles of the national transport policy issued by the executive branch can be adopted and the self-imposed mandate under that policy to craft a national transport master plan can be started. Capacity building programs for local government units must continue and the local roads databases, which are important in prioritizing areas for national government support, must be completed and integrated. To reduce political influence on project implementation, seeking reform champions is necessary and institutionalizing regional development councils' procedures can help.
Keywords: 330; transport infrastructure; public investment program; road transport; rail transport; infrastructure quality